2015
DOI: 10.1002/per.1996
|View full text |Cite
|
Sign up to set email alerts
|

Personality and Friendship Satisfaction in Daily Life: Do Everyday Social Interactions Account for Individual Differences in Friendship Satisfaction?

Abstract: Who are the people who maintain satisfying friendships? And, what are the behaviours that might explain why those people achieve high friendship satisfaction? We examined the associations between personality (self-reports and peer-reports) and friendship satisfaction (self-reports) among 434 students. We also examined whether role personality (how people act with their friends) and quantity and quality of social interactions using ecological momentary assessment mediate the associations between personality and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
133
4
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 127 publications
(149 citation statements)
references
References 69 publications
10
133
4
2
Order By: Relevance
“…We used data from the first wave of the longitudinal Personality and Interpersonal Roles Study (PAIRS; Vazire et al, 2017). Other manuscripts have used the ESM personality state variables (Beck & Jackson, 2018;Breil et al, 2018;Finnigan & Vazire, 2017;Wilson, Harris, & Vazire, 2015;Wilson, Thompson, & Vazire, 2016) and other variables from this dataset (Colman, Vineyard, & Letzring, 2016;Edwards & Holtzman, 2017;Solomon & Vazire, 2016), but this is the first manuscript that examines within-person associations between self-reported and EAR-coded behavior.…”
Section: Methodsmentioning
confidence: 99%
“…We used data from the first wave of the longitudinal Personality and Interpersonal Roles Study (PAIRS; Vazire et al, 2017). Other manuscripts have used the ESM personality state variables (Beck & Jackson, 2018;Breil et al, 2018;Finnigan & Vazire, 2017;Wilson, Harris, & Vazire, 2015;Wilson, Thompson, & Vazire, 2016) and other variables from this dataset (Colman, Vineyard, & Letzring, 2016;Edwards & Holtzman, 2017;Solomon & Vazire, 2016), but this is the first manuscript that examines within-person associations between self-reported and EAR-coded behavior.…”
Section: Methodsmentioning
confidence: 99%
“…There is some evidence that conscientiousness is associated with better friendship quality and less conflict (Berry et al, 2000;Demir & Weitekamp, 2007;Jensen-Campbell & Malcolm, 2007;Wilson et al, 2015), and predicts feeling more positively about one's friendships (Mund & Neyer, 2014). In one study, high conscientiousness at age 12 predicted higher self-reported friendship quality in young adulthood (Lansford, Yu, Pettit, Bates, & Dodge, 2014).…”
Section: Friendship Maintenancementioning
confidence: 99%
“…familiar with: the role of personality traits for friendship development (e.g., Wilson, Harris, & Vazire, 2015). Using this topic as an illustration, we show that many of the same questions that have been examined in the context of romantic relationships can also be examined in the context of friendships.…”
mentioning
confidence: 92%
“…Research on higher-order personality traits (Costa & McCrae, 1992) points to three factors along the affiliation dimension in the interpersonal circumplex (Wiggins, 1979) of highest relevance for social relating competence: Agreeableness, extraversion and neuroticism explain substantial variance in the feelings and perceptions of social interactions (Barrett & Pietromonaco, 1997;Côté & Moskowitz, 1998;Cuperman & Ickes, 2009;Wilson, Harris, & Vazire, 2015). The overall usefulness of the Big Five as predictors of mimicry was also underlined by the findings of Kurzius and Borkenau (2015), but as these authors did not assess emotional mimicry per se, no specific assumptions can be deduced.…”
Section: Proximal Indicators Of Social Relating Competencementioning
confidence: 99%